The impact of personality on intention to leave the nursing profession: A structural equation model - Greinacher, Anja; Helaß, Madeleine; Nikendei, Christoph; Müller, Andreas; Mulfinger, Nadine; Gündel, Harald; Maatouk, Imad (Journal of clinical nursing, 2022)
Aims and objectives To test a mediating effect of compassion satisfaction on the relationship between personality traits (Big Five) and intent to leave. Background Nursing professionals work in high-stress environments and exhibit more emotional distress and mental health disorders than other hospital professionals. This translates to increased intention to leave their profession. Evidence suggests that compassion satisfaction reduces intention to leave. Research also indicates that personality factors are associated with compassion satisfaction and intent to leave. Design Using a cross-sectional design, we collected data from 536 nurses in a maximum-care hospital in Germany via questionnaires; the analyses included 518 participants. Method We applied the structural equation model and followed the STROBE checklist. Results 30% of our study participants reported high intent to leave. Compassion satisfaction mediated the relationship between agreeableness and intent to leave. Openness to experience and neuroticism had positive direct effects on intent to leave. Conclusions The results suggest that high compassion satisfaction levels may decrease intention to leave levels. Personality traits impact compassion satisfaction and intention to leave. Relevance to Clinical Practice Nursing professionals’ compassion satisfaction needs to be improved, for example by resilience training. As personality factors remain relatively stable over time, caregivers need to consider them when identifying appropriate areas of work and responsibility.
First published: 27 August 2021
Gesehen am 11.08.2023